Composite material, electrochemical sensor, preparation method and application

By using multi-wall carbon nanotubes/polyvinyl alcohol/phosphotungstic acid composites as conductive hydrogels, the problem of insufficient stability and adhesion of traditional sensors is solved, and high-precision detection of pyogenes aeruginosa is achieved. in complex biological environments.

CN119307057AActive Publication Date: 2025-01-14MICROBIOLOGY INST OF SHAANXI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411369769.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Traditional electrochemical sensors are inadequate in the detection of Pseudomonas aeruginosa infection in the field of biomedical science, which is difficult to meet the high-precision detection needs in complex biological systems.

Method used

Multi-wall carbon nanotubes/polyvinyl alcohol/phosphotungstic acid composite materials are used as conductive hydrogels. The formation of strong hydrogen bonds between phosphotungstic acid and polyvinyl alcohol can enhance adhesion, and optimize the conductive network structure to improve the sensitivity of the sensor. and stability.

Benefits of technology

The linear detection range of Pseudolyticin is achieved from 5-100μM/L, with a detection limit as low as 1.67μM/L, with anti-interference and stability, and is suitable for a variety of complex electrolyte environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307057A_ABST
    Figure CN119307057A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical detection, and relates to a composite material, an electrochemical sensor, a preparation method and application. The invention provides a multiwalled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material. The multiwalled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material is composed of carboxylated multiwalled carbon nanotubes, polyvinyl alcohol and phosphotungstic acid. According to the composite material, phosphotungstic acid is introduced and can be complexed with polyvinyl alcohol through hydrogen-bond interaction to form a stable hydrogel framework, so that the important problems that a multi-walled carbon nanotube / polyvinyl alcohol composite material is poor in film-forming adhesion, unstable in sensing characteristic and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical detection, and relates to a composite material, an electrochemical sensor, a preparation method and an application. Background Art

[0002] In the biomedical field, especially for the rapid detection of pathogens, it is crucial to develop efficient, sensitive and easy-to-use detection technologies. Pseudomonas aeruginosa (PA) is a common Gram-negative pathogen. Its infection is common in patients with cystic fibrosis (DFT), diabetic foot and immunocompromised patients, posing a serious threat to public health. Pyocyanin (PCN) is a characteristic marker of PA secretion, and its quantitative detection is of great significance for timely diagnosis and control of infection. However, traditional detection methods such as high-performance liquid chromatography (HPLC) and spectrophotometry are accurate but complex and time-consuming, making it difficult to meet the needs of clinical and on-site rapid detection.

[0003] In recent years, electrochemical sensors have shown great potential in the field of biosensing due to their advantages such as rapid response, high sensitivity and low cost. Carbon nanotubes (CNTs), especially multi-walled carbon nanotubes (MWCNTs), have become ideal materials for constructing high-performance electrochemical sensing interfaces due to their excellent electron conduction ability and large specific surface area. The MWCNTs / PVA composite material formed by combining with polyvinyl alcohol (PVA) not only inherits the conductivity and stability of MWCNTs, but also further broadens its application range in the field of biosensing through the excellent film-forming property and biocompatibility of PVA. However, the application of MWCNTs / PVA in electrochemical sensors still faces many challenges. Stability problem: MWCNTs are not firmly fixed on the conductive substrate and are easy to fall off, resulting in unstable sensor performance and affecting the reliability of long-term use. Insufficient adhesion: Although PVA hydrogel has good biocompatibility, its adhesion to the smooth conductive substrate is weak, especially in a humid environment, and it is easy to swell and peel, which seriously limits the practical application of the sensor. Sensing performance needs to be improved: Sensors constructed solely based on MWCNTs / PVA composite materials still have room for improvement in terms of sensitivity, detection range and anti-interference ability, and are unable to meet the high-precision detection requirements in complex biological systems. Summary of the invention

[0004] To overcome the above difficulties, the present invention proposes a MWCNTs / PVA / PTA composite material, and based on this material as a conductive hydrogel coated on a conductive electrode to construct a high-performance electrochemical sensor. As a type of polyoxometalates (POMs), phosphotungstic acid (PTA) has a unique Keggin structure and rich oxygen atom bonding mode, which can form strong hydrogen bonds with PVA, effectively reducing the crystallinity of PVA, thereby enhancing the adhesion between the hydrogel and the conductive substrate. At the same time, the introduction of PTA also optimizes the conductive network structure, increases the accessible active sites, and further improves the sensitivity and stability of the sensor.

[0005] On the one hand, the present invention relates to a multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material, which is composed of carboxylated multi-walled carbon nanotubes, polyvinyl alcohol and phosphotungstic acid.

[0006] In the composite material method provided by the present invention, there is no particular restriction on the ratio of carboxylated multi-walled carbon nanotubes and polyvinyl alcohol. Depending on the different objects of electrochemical detection, those skilled in the art can adjust the mass ratio of carboxylated multi-walled carbon nanotubes and polyvinyl alcohol as needed to achieve suitable electrical conductivity and mechanical strength. Generally speaking, when the mass ratio of carboxylated multi-walled carbon nanotubes and polyvinyl alcohol is 1:0.01 to 0.5, it can be used for electrochemical detection and has good electrical conductivity and mechanical strength.

[0007] The present invention improves the adhesion, sensitivity and stability of the MWCNTs / PVA composite material in the electrochemical sensor by introducing phosphotungstic acid to form a suitable structure with polyvinyl alcohol. Those skilled in the art can select a suitable mass ratio of carboxylated multi-walled carbon nanotubes and polyvinyl alcohol according to different electrochemical detection objects, and then add phosphotungstic acid so that the mass ratio of polyvinyl alcohol and phosphotungstic acid is 10-60%, so as to obtain a suitable multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material.

[0008] Furthermore, in the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material provided by the present invention, the mass ratio of carboxylated multi-walled carbon nanotubes, polyvinyl alcohol and phosphotungstic acid is 1:0.2:1-5.

[0009] On the other hand, the present invention relates to a method for preparing the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material, which comprises: dispersing carboxylated multi-walled carbon nanotubes into an aqueous solution containing SDS, adding polyvinyl alcohol and heating to dissolve to form a solution, and adding phosphotungstic acid after cooling to form a composite hydrogel.

[0010] On the other hand, the present invention relates to the use of the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material in improving the performance of an electrochemical sensor, wherein the performance is at least one of sensitivity, anti-interference, stability and reproducibility.

[0011] Furthermore, in the application provided by the present invention, the anti-interference property refers to the ability of the electrochemical sensor to work stably in a variety of complex electrolyte environments.

[0012] Furthermore, in the application provided by the present invention, the plurality of complex electrolyte environments include PBS, LB broth and artificial saliva.

[0013] On the other hand, the present invention relates to an electrochemical sensor, comprising a working electrode, the surface of the working electrode being coated with the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material.

[0014] On the other hand, the present invention relates to an electrochemical sensor for detecting pyocyanin, comprising a working electrode, the surface of the working electrode being coated with the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material.

[0015] Furthermore, in the electrochemical sensor for detecting pyocyanin provided by the present invention, the electrochemical sensor for detecting pyocyanin has a linear detection range of 5 to 100 μM / L for pyocyanin, and a detection limit as low as 1.63 μM / L.

[0016] On the other hand, the present invention relates to the use of phosphotungstic acid in improving the performance of multi-walled carbon nanotube / polyvinyl alcohol composite hydrogel, the mass ratio of polyvinyl alcohol to phosphotungstic acid is 0.2:1-5; the incorporation of the phosphotungstic acid improves at least one of the crystallinity, adhesion ability, and the number of accessible active sites of polyvinyl alcohol in the multi-walled carbon nanotube / polyvinyl alcohol composite hydrogel.

[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:

[0018] The adhesion of hydrogels can be improved by surface modification, bridging polymers, topological adhesion, and incorporation of nanomaterials. The first three methods all insert an intermediate layer between the hydrogel and the substrate to form a sandwich structure with strong adhesion through the action of the intermediate layer, which does not improve the direct adhesion ability of the hydrogel, and the addition of the intermediate layer material will reduce the biocompatibility and limit the use environment (such as pH and temperature). However, the mechanism of action of nanoparticles is to complex with polymers through their surface functional groups, change the polymer structure and fragment dynamics, such as reducing the crystallinity of the hydrogel, and achieve its close binding with the substrate. In addition, nanoparticle composite hydrogels can improve conductivity, magnetic treatment and antibacterial properties, and expand the application of hydrogels in the field of sensing. Polyoxometalates (POMs) are nanoscale metal oxide clusters, and phosphotungstic acid (PTA) is a typical Keggin structure, in which oxygen atoms have multiple bonding modes and can form hydrogen bonds with the ideal hydrogel material polyvinyl alcohol (PVA), reduce the crystallinity of PVA, weaken the internal stress during film curing, and promote it to form a strong adhesion structure with the substrate. Therefore, the present invention solves the above problems by constructing a MWCNTs / PVA / PTA composite material through self-assembly as a conductive hydrogel, and prepares an electrochemical sensor of MWCNTs / PVA / PTA based on this. The MWCNTs / PVA / PTA sensor can achieve linear detection of PCN concentrations in the range of 5-100 μM / L in a variety of electrolyte environments, and the detection limit (LOD) is as low as 1.67 μM / L. The sensor also has certain anti-interference, stability and reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 SEM images and element distribution diagrams of different composite materials. AB is the SEM image of MWCNTs; CD is the SEM image of MWCNTs / PVA; EF is the SEM image of MWCNTs / PVA / PTA4; GH is the SEM image of MWCNTs / PVA / PTA8; I is the element mapping image of MWCNTs / PVA / PTA4.

[0021] Figure 2 The three-dimensional and two-dimensional AFM images of the electrochemical sensor. A is MWCNTs / PVA; B is MWCNTs / PVA / PTA4; C is MWCNTs / PVA / PTA8.

[0022] Figure 3 The FT-IR test results of the electrochemical sensor. Among them, A is the FTIR of the electrochemical sensor; B is the WAXS of the electrochemical sensor; C is the I(q) of the electrochemical sensor -1 / 2 -q 2 curve; D is the C1s XPS spectrum of MWCNTs / PVA; E is the O1s XPS spectrum of MWCNTs / PVA; F is the W 4f XPS spectrum of MWCNTs / PVA; G is the C1sXPS spectrum of MWCNTs / PVA4; H is the O1s XPS spectrum of MWCNTs / PVA4; I is the W 4f XPS spectrum of MWCNTs / PVA4.

[0023] Figure 4 The sensing performance of the sensor for measuring PCN concentration in different electrolyte environments was evaluated by square wave voltammetry (SWV). A is the SWV current response of PCN at 5-100 μM in PBS medium; B is the SWV current response of PCN at 10-100 μM in LB medium; C is the SWV current response of PCN in the range of 10-100 μM in artificial saliva medium; D is the calibration curve of the three media, and the error bars represent the standard deviation between three repeated measurements; E is the SWV current response and peak potential of PCN in PBS with different pH values; F is the SWV current response of the supernatant of PA culture medium (including PCN).

[0024] Figure 5 The stability test of MWCNTs / PVA / PTA composite materials. A is the selective SWV reaction of MWCNTs / PVA / PTA4 to 50μM PCN under the interference of the same concentration; B is the stability of MWCNTs / PVA / PTA4 to 50μM PCN; C is the reproducibility of MWCNTs / PVA / PTA4 prepared from different batches of hydrogels.

[0025] Figure 6 Comparison of peak current of electrochemical sensors under different modified materials. A is MWCNTs; B is MWCNTs / PVA; C is MWCNTs / PVA / PTA4.

[0026] Figure 7 The OM images of the electrochemical sensor surface after preparation at different times. A is MWCNTs modified for 1 day; B is MWCNTs / PVA modified for 1 day; C is MWCNTs / PVA / PTA4 modified for 1 day; D is MWCNTs / PVA / PTA4 modified for 2 days; E is MWCNTs / PVA / PTA4 modified for 3 days; F is MWCNTs / PVA / PTA4 modified for 4 days. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials are available on the market unless otherwise specified, and the % in the following examples are all mass percentages unless otherwise specified.

[0028] Example 1

[0029] This example provides the preparation of MWCNTs / PVA / PTA composite materials and electrochemical sensors.

[0030] Raw materials: carboxylated multi-walled carbon nanotubes, purchased from Xianfeng Nanotechnology Co., Ltd., Jiangsu Province, China; sodium dodecyl sulfate (SDS), polyvinyl alcohol (PVA, hydrolysis degree 99%), phosphotungstic acid hydrate (PTA, H3O 40 PW 12 ·xH2O), pyocyanin (PCN, CRS), were purchased from Aladdin Chemical Reagent Co., Ltd. All solutions were prepared with Milli-Q grade water (Millipore water purification system Z18 MΩ, Milli-Q, Millipore, Billerica, MA).

[0031] 0.01-0.5g of MWCNTs functionalized with carboxyl polar groups (i.e., carboxylated multi-walled carbon nanotubes) were dispersed in 10mL SDS aqueous solution, stirred at high speed for 30min, and then treated under ultrasonic conditions to prepare a series of MWCNTs uniform dispersions of different concentrations. Then 0.02-1g of PVA was added to the above dispersion, stirred in a water bath at 95°C for 1h to ensure that PVA was completely dissolved, and PTA was added and stirred at the same speed for 30-180min. MWCNTs / PVA / PTA composite hydrogels of different proportions were successfully prepared according to the added PTA content. As the amount of PTA added increased, the corresponding samples were labeled as MWCNTs / PVA / PTA2, MWCNTs / PVA / PTA4, MWCNTs / PVA / PTA8, and MWCNTs / PVA / PTA10. The mass ratios of MWCNTs functionalized with carboxyl polar groups, polyvinyl alcohol and phosphotungstic acid are 1:0.2:1, 1:0.2:2, 1:0.2:4 and 1:0.2:5 respectively. In the following examples, unless otherwise stated, MWCNTs / PVA / PTA composite materials all refer to MWCNTs / PVA / PTA4 composite materials.

[0032] The electrochemical performance measurements were performed on a China electrochemical workstation (CHI660E, Chenhua Instrument Co., Ltd., China) with a conventional three-electrode cell containing 1× phosphate buffer (PBS, pH 7.3), Ag / AgCl as the reference electrode, and a piece of platinum as the counter electrode.

[0033] Take 5 μL of the above composite hydrogel and drop it on the pre-cleaned 0.5 cm×0.5 cm ITO working electrode surface. After natural drying at room temperature, perform freeze-thaw cycles. The obtained sensor can be used for the next electrochemical test.

[0034] Example 2

[0035] This example provides a performance comparison of three composite materials, MWCNTs, MWCNTs / PVA, and MWCNTs / PVA / PTA, in electrochemical sensors.

[0036] Raw materials: Pyocyanin (PCN) was purified from Pseudomonas aeruginosa (PA).

[0037] When the sensor prepared by MWCNTs dispersion was tested, the material fell off in uneven blocks; the MWCNTs / PVA sensor also had the composite film fall off after swelling due to water absorption. Figure 6 As shown in the figure, neither of these two sensors can achieve accurate detection of PCN.

[0038] Two important issues were found for the prepared MWCNTs / PVA / PTA hydrogel. First, there is a clear correlation between the state of the hydrogel film and the number of days it has been left standing. Through OM, it can be observed that the films prepared by dripping the hydrogels left standing for one day and two days have obvious agglomeration. When the standing time exceeds 3 days, the agglomeration can be significantly improved ( Figure 7 ). Secondly, the stability of MWCNTs / PVA / PTA hydrogel film is closely related to the PTA content. Based on the above phenomenon, this study first investigated the effects of the number of days the hydrogel was left to stand, the introduction of PTA stabilizer, and the number of freeze-thaw cycles on the sensor and its related mechanism of action. Figure 7 As shown in A, the response current of the hydrogel-prepared sensor that was left to stand for 4 days or more tended to be stable, and no aggregation was observed on the surface.

[0039] Example 3

[0040] This example provides an analysis of the electrode adhesion mechanism of three composite materials: MWCNTs, MWCNTs / PVA, and MWCNTs / PVA / PTA.

[0041] SEM observation of electrode surface morphology of different material systems Figure 1 As shown. Figure 1 C and Figure 1As shown in D, compared with the MWCNTs surface which is composed of a large number of agglomerated and intertwined strip carbon nanotubes ( Figure 1 A and Figure 1 B), the surface of MWCNTs / PVA is smooth, and the film-forming effect can be clearly observed, proving that PVA physically cross-links to form hydrogels during the freeze-thaw process, and the number of CNTs observed on the surface is reduced at the same scale, which may be due to the fact that most CNTs are wrapped inside the hydrogel. After adding different proportions of PTA into the system, the number of strip-shaped CNTs on the surface increases instead. Figure 1 E and Figure 1 F, the film quality of MWCNTs / PVA / PTA4 surface is reduced, more CNTs are exposed on the surface, and the number of accessible active sites increases. Figure 1 I found that the CNTs, PTA, and SDS dispersant in the hydrogel were uniformly distributed on the electrode surface. Further increasing the PTA content in the system, such as Figure 1 G and Figure 1 As shown in Figure H, the CNTs on the surface of MWCNTs / PVA / PTA8 did not continue to increase according to the trend of MWCNTs / PVA / PTA4, but instead showed regional agglomeration. It is speculated that after the content of PTA increases, PTA itself will be enriched, causing the CNTs to agglomerate in this area, and the uniformity of the surface material will deteriorate.

[0042] Atomic force microscopy (AFM) test results can also prove the above analysis. Figure 2 A shows the surface morphology of MWCNTs / PVA, with an Rq of 30.6nm. From the 2D morphology, it can be seen that the CNTs are embedded in the hydrogel. After adding PTA, the roughness of the material surface increases to varying degrees. Figure 2 As shown in Figure B, the Rq of MWCNTs / PVA / PTA4 increases to 38.5 nm. From the 3D morphology, it can be clearly observed that the peaks are different from those of MWCNTs / PVA, and the particle size on the surface increases in the 2D morphology. This may be due to the decrease in the crystallinity of PVA after the addition of PTA, and the CNTs are exposed again. Figure 2 C shows the surface morphology of MWCNTs / PVA / PTA8. The addition of PTA doubles the h content, and its Rq increases from 38.5nm to 50.8nm. The sharp small peaks in MWCNTs / PVA / PTA4 are replaced by smooth large peaks in the 3D morphology image. No exposed CNTs are clearly observed in the 2D morphology image, which is consistent with the SEM speculation that PTA itself will be enriched and cause CNTs to agglomerate in this area.

[0043] In order to better understand the internal state of the three hydrogel systems, FT-IR technology was used. Figure 3As shown in A, after the introduction of PTA, the infrared spectrum showed 981, 896 cm -1 W=O appears at d Tensile vibration and WO b -W stretching vibration peaks, proving that PTA was successfully introduced into the hydrogel system. -1 The asymmetric stretching vibration peak belonging to CO gradually becomes smaller with the addition of PTA, proving that PTA hinders the crystallization of PVA during the physical cross-linking process, so the amount of CO in the conductive hydrogel network decreases.

[0044] The phase separation morphology of the blend membrane was analyzed using WAXS technology. Figure 3 As shown in Figure B, the characteristic peak broadened after adding PTA. The characteristic scattering peak of MWCNTs / PVA / PTA4 shifted to large q, indicating that the phase separation size of PTA and PVA became smaller after blending, forming a uniform blend phase. However, in the MWCNTs / PVA / PTA8 system, the characteristic peak shifted to the small q region, the phase separation size of PTA and PVA became larger, and the two did not merge well, which is consistent with the SEM conclusion.

[0045] XPS was used to analyze the surface chemical bond states of electrodes modified with different hydrogel systems. Figure 3 The O1s spectrum of E-3H showed a typical bond of O=C from carboxyl, a typical bond of OC from PVA, and a typical bond of O=W from PTA appeared in the O1s spectrum of MWCNTs / PVA / PTA4. Figure 3 In the W4f spectrum shown in F-3I, no W-related bonding was observed in MWCNTs / PVA, and there was a binding energy peak of WO3 self-orbital splitting in MWCNTs / PVA / PTA4. In addition, there were typical bonds of WC, indicating that part of PTA was loaded on the carbon nanotubes during the anchoring process. This can also explain the phenomenon in the AFM results that the self-enrichment process of PTA will cause CNTs to agglomerate near it.

[0046] Example 3

[0047] In this example, square wave voltammetry (SWV) was used to characterize the sensing performance of an electrochemical sensor made of MWCNTs / PVA / PTA composite material for measuring PCN concentration in different electrolyte environments.

[0048] like Figure 4 As shown in A, when tested in PBS, an oxidation peak appeared at 0.34V, and its oxidation peak current gradually increased with increasing concentration. In the range of 5μM to 50μM and 50μM to 100μM, its peak current showed a good linear relationship with PCN concentration ( Figure 4 D), correlation coefficient R 2The LOD of this sensor in PBS is 1.67 μM, covering the PCN concentration range of 5-100 μM in clinical infection. The slope of the standard curve at higher concentrations is smaller than that at low concentrations, indicating that the detection sensitivity is reduced at high concentrations. PCN is a marker secretion of PA, so the same test was performed in LB broth, a commonly used PA culture medium. Figure 4 As shown in B, the test results in LB broth showed the same pattern as those in PBS. The PCN oxidation behavior was determined at 0.384 V, and the oxidation peak current increased with increasing concentration. The fitting equation is I = 0.13 (C / μM) + 0.7, R 2 The value of PA colonization is 0.996, and the LOD is 2.71 μM. Since PA colonization is often found in sputum in lung infections, artificial saliva is the sample closest to sputum. Sensor tests were also conducted in artificial saliva environments, such as Figure 4 As shown in Figure C, the PCN oxidation peak was observed at 0.354V, the concentration standard R2 was 0.995, and the LOD was 3.63μM. However, the sensitivity in LB broth and artificial saliva was lower than the test results in PBS environment. The reason may be that the components of the electrolytes of these two electrolytes include proteins and peptides in addition to ions. These biomacromolecules will affect the adsorption of the analyte, and the viscosity of artificial saliva is greater than that of the other two electrolytes, which will hinder the diffusion of PCN from the electrolyte to the electrode surface. Therefore, the sensitivity of saliva is the lowest.

[0049] The MWCNTs / PVA / PTA4 in Na + , K + The selectivity of PCN in the presence of various organic and inorganic substances such as AA, Urea, and glucose. Figure 5 As shown in A, when the same concentration of interfering substances is added to the solution environment containing PCN, the current deviation caused by any interfering substance does not exceed ±10%. The results show that the developed sensor has good anti-interference ability. In order to verify the stability and reproducibility of the sensor. The sensor prepared on the same day was stored in the air for different days and then tested. On the sixth day, the electrode maintained 88.44% of the initial value, indicating that the sensor has long-term stability ( Figure 5 B) Using different batches of hydrogel to prepare sensors to investigate reproducibility, e.g. Figure 5 C, The current response deviation of the hydrogels corresponding to five different batches of hydrogels under the same conditions does not exceed ±5%. MWCNTs, PVA and PTA in the hydrogel system are highly stable in the air environment and are not easy to volatilize, which makes the sensor have good stability and reproducibility.

[0050] The present invention provides a MWCNTs / PVA / PTA hydrogel and applies it to the field of biosensing for the first time. The present invention discloses the mechanism of PTA modulating the adhesion and sensing sensitivity of the hydrogel. The constructed sensor is used to detect PCN in a variety of electrolyte environments such as PBS, LB, and artificial saliva, with a linear detection range of 5-100 μM / L and a minimum detection limit of 1.67 μM / L. More importantly, it was found that PTA suppressed the low adhesion of PVA caused by internal stress, promoted the transport efficiency of protons in the conductive network, and broadened the application range of MWCNTs / PVA / PTA sensors in various solution environment stability tests. Therefore, the MWCNTs / PVA / PTA sensor prepared by the present invention has a wide range of application potential for detecting PCN, and the proposed PVA composite PTA action mechanism has opened up more ways for further in-depth research on composite hydrogel sensing films.

[0051] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.

Claims

1. A multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material, characterized in that: It is composed of carboxylated multi-walled carbon nanotubes, polyvinyl alcohol and phosphotungstic acid.

2. The multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material according to claim 1, characterized in that: The mass ratio of carboxylated multi-walled carbon nanotubes, polyvinyl alcohol and phosphotungstic acid is 1:0.2:1-5.

3. A method for preparing the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material according to any one of claims 1 to 2, characterized in that: include: The carboxylated multi-walled carbon nanotubes are dispersed in an aqueous solution containing SDS, polyvinyl alcohol is added and heated to dissolve to form a solution, and after cooling, phosphotungstic acid is added to form a composite hydrogel.

4. Use of the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material according to any one of claims 1 to 2 in improving the performance of an electrochemical sensor, characterized in that: The performance is at least one of sensitivity, anti-interference, stability and reproducibility.

5. The use according to claim 4, characterized in that: The anti-interference property refers to the ability of the electrochemical sensor to work stably in a variety of complex electrolyte environments.

6. The use according to claim 5, characterized in that: The various complex electrolyte environments include PBS, LB broth and artificial saliva.

7. An electrochemical sensor comprising a working electrode, characterized in that: The surface of the working electrode is coated with the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material according to any one of claims 1 to 2.

8. An electrochemical sensor for detecting pyocyanin, comprising a working electrode, characterized in that: The surface of the working electrode is coated with the multi-walled carbon nanotube / polyvinyl alcohol / phosphotungstic acid composite material according to any one of claims 1 to 2.

9. The electrochemical sensor for detecting pyocyanin according to claim 8, characterized in that: The electrochemical sensor for detecting pyocyanin has a linear detection range of 5 to 100 μM / L for pyocyanin, and a detection limit as low as 1.63 μM / L.

10. Application of phosphotungstic acid in improving the performance of multi-walled carbon nanotube / polyvinyl alcohol composite hydrogel, characterized in that: The mass ratio of polyvinyl alcohol to phosphotungstic acid is 0.2:1-5; the incorporation of the phosphotungstic acid improves at least one of the crystallinity, adhesion ability and the number of accessible active sites of the polyvinyl alcohol in the multi-walled carbon nanotube / polyvinyl alcohol composite hydrogel.

Citation Information

Patent Citations

  • Preparation method of phosphotungstic acid / polyvinyl alcohol composite proton exchange membrane

    CN102847449A

  • Preparation method of carboxylic multiwalled carbon nanotube / PBS micro-nano fiber / polyvinyl alcohol composite conductive hydrogel

    CN108822457A

  • Phosphomolybdic acid / polymer / carbon nanotube composite conductive hydrogel, preparation method thereof and application thereof in all-solid-state flexible super capacitor

    CN111029164A

  • Composition and method of producing polymer proton-conducting composite material

    RU2565688C1